The Effect of Proactive Market Orientation on Company Performance: The Case of Medium and Large Manufacturing Companies in Ethiopia - Durie, Aschalew Degoma; Beshir, Elias Shetemam (International Journal of Management and Sustainability, 2018)
The objective of this study was to examine the effects of proactive market orientations on companies’ performances to come up with possible managerial and theoretical insights as to how manufacturing companies become proactive in formulating and implementing their marketing strategies of these days. Quantitative research approach with explanatory research design was employed. The variables used in the research were formulated based on the extant literature review which includes proactive customer orientations, proactive competitors’ orientations, and market-based innovations as determinant variables and the companies’ performances as an outcome variable. Textile and leather companies become the center of attention for this study because being proactive is the demand of the competition for such industries as fashion dictates the needs of customers and the dynamism of the competition in general. Simple random sampling technique was applied and a total of 76 qualified questionnaires were used for the data analysis. Multiple linear regression analysis was used for data analysis and SPSS version 22 was used for the purpose. Based on the result, all of the three independent variables are found to significantly affect the dependent variable while proactive customer orientation is the strongest predictor among the three predictor variables. Hence, the managerial implication is implied for the companies that while being proactive is essential in general, being proactive in understanding the current needs of customers and predicting the changes in those needs in the future is particularly important in order for those companies to remain relevant and sustainable in the market.